Artificial Taste: Advances and Innovative Applications in Healthcare - Letao Wang; Yuzhang Li; Yao Zhang; Bin Zheng (Applied Sciences)
Background: Scientists have recently developed a technology that induces artificial taste through electronic stimulation. However, scattered reports have made it difficult to comprehensively understand the technology’s details and appreciate its potential applications in healthcare. To address these gaps, a meta-review was conducted. We re-viewed the current literatures on the technology behind artificial taste. Targeted original research papers were analyzed, with data extracted to address five key aspects: interface design, stimulation parameters, sensation verification results, applications to health problems, and potential side effects in human subjects. Results: A total of 19 relevant papers were identified. Eight studies focused on tongue-tip electrode interfaces, while others integrated technology into eating utensils. Eleven studies examined stimulation frequencies (50–1000 Hz), with five altering temperature and two changing water color to enhance taste perception. Only six studies reported verification results, showing that most participants perceived sour and salty tastes, mild bitter responses, and unreliable sweet evocation. Sixteen papers discussed applications in healthcare (dietary and weight management), entertainment (food and beverage sampling), and education. Side effects included reduced sensitivity after repeated trials and occasional discomfort from excessive stimulation, though no immediate tissue damage was reported. Conclusions: Artificial taste technology offers an innovative approach to managing food and beverage intake without compromising taste sensations. When applied on a large scale, it holds significant potential for regulating eating behaviors and providing novel strategies for addressing chronic health issues associated with diet.